2020
DOI: 10.1055/s-0040-1715098
|View full text |Cite
|
Sign up to set email alerts
|

Gout As a Predictor of Total Knee Arthroplasty Outcomes and Costs

Abstract: Gout is the most common inflammatory arthritis and affects approximately 4% of the U.S. population. As the prevalence of gout and the number of total knee arthroplasties (TKAs) performed continue to increase, the literature on TKA in patients with gout remains scant. The purpose of this study was to evaluate the outcomes of patients with gout following TKA at a population level, that is, how patient with gout fair after TKA. We hypothesized that patients with gout have higher rates of complications and higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…Notably, gout patients had a decreased risk of pulmonary emboli (OR: 0.835). These findings support the hypothesis that gout patients undergoing TKA face elevated postoperative complication rates and increased costs [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…Notably, gout patients had a decreased risk of pulmonary emboli (OR: 0.835). These findings support the hypothesis that gout patients undergoing TKA face elevated postoperative complication rates and increased costs [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…Several studies describe an association between gout and a higher risk of complications after TKA. Rosas et al analyzed more than 7,000 patients with gout and found significantly greater postsurgery costs and increased odds (results reported as odds ratio, 95% confidence interval) of infection (1.2, 1.03-1.4), cardiac arrest (1.3, 1.1-1.6), pneumonia (1.1, 1.07-1.2), and development of capsulitis after TKA (1.2, 1.04-1.4), compared with patients without gout after TKA 76 . Similarly, Chen et al found a higher rate of renal complications and poor wound healing in TKA patients with gout compared with those without gout 77 .…”
Section: Treatment Of Gout Cppd Disease and Pji And Associated Outcomesmentioning
confidence: 99%